2014
DOI: 10.1007/s11252-014-0390-z
|View full text |Cite
|
Sign up to set email alerts
|

Avian metapopulation dynamics in a fragmented urbanizing landscape

Abstract: As urbanization transforms landscapes around the globe, we are challenged to find ways for urban habitats to contribute to ongoing wildlife conservation efforts. Yet aside from basic distributions and relative abundance, we know little about the population dynamics of most species occupying urban habitats and almost nothing about the extent to which local populations serve as source or sink habitats. We analyzed the spatial synchrony and persistence of local populations of 16 avian species breeding in 14 matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…In case of N. brevicollis, the forest fragments in the urbanised habitat had higher activity densities, so they can even serve as population source, not sink. This is an in-teresting phenomenon, because urbanised habitats are often considered sink habitats (Padilla & Rosewald 2015). Carabids in the northern temperate region are generally active during spring and late summer (Penney 1969, Thiele 1977.…”
Section: Discussionmentioning
confidence: 99%
“…In case of N. brevicollis, the forest fragments in the urbanised habitat had higher activity densities, so they can even serve as population source, not sink. This is an in-teresting phenomenon, because urbanised habitats are often considered sink habitats (Padilla & Rosewald 2015). Carabids in the northern temperate region are generally active during spring and late summer (Penney 1969, Thiele 1977.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, habitat fragmentation has allowed evolutionary forces to generate changes in phenotypic traits, influencing characteristics such as dispersal propensities (Cheptou, Hargreaves, Bonte, & Jacquemyn, 2017) or life history traits (De Roissart, Wybouw, Renault, Leeuwen, & Bonte, 2016), as well as broader eco-evolutionary processes (Fronhofer & Altermatt, 2017). The metapopulation concept has proven broadly applicable in urbanization-associated habitat fragmentation scenarios, facilitating an improved understanding of how landscape alterations can affect regional population processes for many taxa, such as birds (Millsap, 2018;Padilla & Rodewald, 2015) and amphibians (Cox, Maes, Calster, & Mergeay, 2017;Hale et al, 2013;Heard, McCarthy, Scroggie, Baumgartner, & Parris, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Broadfoot, Rosatte and O'Leary (2001) found very dense raccoon (Procyon lotor) and skunk (Mephitis mephitis) populations in Ontario, Canada, where they are subject to increased disease Ecological spillover dynamics of organisms from urban to natural landscapes | 5 incidence within this urban environment, and may subsequently transmit disease back to populations in surrounding areas. Padilla and Rodewald (2015) found evidence that urban areas may be acting as sinks for avian species in riparian forests of central Ohio, but that the number and quality of habitat patches within the urban matrix influences longer-term trends in urban populations. In the Swiss canto of Aargau, Altermatt (2012) concluded that urban sites likely serve as sinks for butterflies within the overall habitat matrix, drawing immigrants from adjacent, higher-quality habitats.…”
Section: Resultsmentioning
confidence: 97%